Patient Safety Culture as A Mediator Between Leadership and Incident Reporting - Kurniati Dameria; Margaretha Banowati Talim; Paulus Susilo Sugiarto (Journal of Public Health Sciences, 2026)
This study investigates the influence of transformational leadership on patient safety incident reporting among nurses in the inpatient units of Charitas Group hospitals, with a focus on the mediating role of patient safety culture. Using a sequential explanatory mixed-methods design, the research integrates quantitative survey data from 232 nurses and qualitative insights from 16 key informants, including unit heads and safety committee leaders. Structural Equation Modeling and Sobel test results reveal that transformational leadership has a positive effect on patient safety culture but a paradoxically negative direct effect on incident reporting. Patient safety culture significantly mediates this relationship, underscoring the role of organizational climate in translating leadership into safety behaviors. Qualitative findings illuminate this paradox, revealing stark unit-level differences such as in the Pharmacy unit, where psychological safety and open dialogue are strongly fostered, while in other units, fear, silence, and inadequate follow-up persist. The study finds that institutional values are not consistently reflected in daily practices, limiting cultural transformation. This study contributes to the limited literature in Indonesia by highlighting how leadership must be embedded in safe and responsive environments to encourage safety behavior. Recommendations include strengthening leadership presence and follow-through, enhancing safety committee roles, and conducting routine audits to promote a just and learning culture. The findings provide actionable insights for hospital policy, leadership training, and efforts to improve organizational safety in healthcare settings.